Discontinuation of Chronic Opiate Therapy After Successful Spinal Cord Stimulation Is Highly Dependent Upon the Daily Opioid Dose. Issue 8 (13th August 2019) - Simopoulos, Thomas; Sharma, Sanjiv; Wootton, Raymond Joshua; Orhurhu, Vwaire; Aner, Moris; Gill, Jatinder S
Abstract: Objectives: The aim of this study was to determine if any of the factors recorded on a standard clinical history of a patient considered for spinal cord stimulation (SCS) would be associated with reduction or cessation of opioids following implantation. Design: Retrospective, single academic center. Methods: Patients included in the chart analysis underwent implantation of percutaneous SCS devices from 1999 to 2015 with follow‐up until the end of September 2018. Patients who achieved at least an average of 50% pain reduction were included for analysis of daily opioid intake. Patients were then divided into 4 groups that included no opioid use, stable opioid daily dose, weaned opioid dose, and complete cessation of opioids. Statistical methods were used to analyze for associations between opioid intake after SCS insertion and usual elements of a clinical history, including adjuvant medications, numeric pain rating, past medical history, psychiatric illness, substance abuse, employment, and smoking history. Results: In a group of 261 patients who had undergone implantation, 214 met the criteria for analysis and had a median age of 50 years, with majority having the diagnoses of failed back surgery syndrome and complex regional pain syndrome. The only factor that was associated with complete cessation of opioid use was a median dose of 30 mg of morphine per day ( P < 0.01) and was observed in 15% of subjects who used opioids preoperatively. Conclusion: The elimination of opioid dependence following initiation of SCS therapy is highly dependent on the daily dose.